The Early Holocene Vertebrate Faunas from Seropan Cave, Gunung Sewu, Yogyakarta, Indonesia - Setiyabudi, Erick; Prasthisto, Bambang; Kurniawan, Iwan; Jatmiko, Teguh (Geological Agency, 2018)
DOI: 10.17014/ijog.5.1.33-45An excavation of a vertebrate fossil site was carried out in 2012 in the Seropan Cave of Gunung Sewu karst area, Wonosari, Yogyakarta. Among the discovered mammal fossils there are Cervus sp., Sus verrucosus, Bubalus sp., and Panthera cf. pardus. Small mammal bone fragments of GSP (Gua Seropan/Seropan Cave) Nos. 38, 67, 91-113 have been analyzed for C14 radiocarbon age dating, which gave a date of 9,450 Â± 400 yrs. B.P. or Early Holocene. The Seropan fauna is part of the succession series of Braholo fauna that migrated before the Late Pleistocene, and was isolated after the last Ice Age. The Seropan fauna developed and adapted their morphology to the local habitat.